Stopping rape : towards a comprehensive policy - Walby, Sylvia (Policy Press, 2015)
Epdf available Open Access under CC-BY-NC licence. This book offers a comprehensive guide to the international policies developed to stop rape, together with case studies on their effectiveness in practice. Engaging with the legal and criminal justice systems, health services, specialised services for victim-survivors, educational and cultural outreach, and more, it brings together both theory and real-world evidence to build a thorough picture of worldwide efforts to fight rape in all its contexts.